The effectiveness of TiO2 additions to mortar to maintain initial conditions in terms of its reflectance to solar radiation - Dantas, Sérgio Roberto Andrade (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2017)
Contact of facades with degradation agents and direct incidence of ultraviolet radiation on external coatings make them more opaque over time, affecting their colour and reflectance characteristics. This study evaluated the effect of adding different TiO2 contents to mortars applied in concrete substrates in order to verify the reflectance maintenance on surfaces after exposure over time. Mortar with different concentrations of TiO2 (1%, 5%, 10%) were produced in relation to the total dry premix, added as a powder and compared to unpainted mortar without TiO2 (type “A”) and painted mortar without TiO2 (type “B”), both used as a reference for colour and reflectance. Exposed over 16 months to climate conditions in São Paulo, regarding the maintenance of reflectance and solar radiation, the results showed that type “B” (0%TiO2) painted mortar presented the best performance. Type “C” (1%TiO2) and type “D” (5%TiO2) unpainted mortar remained more stable. Type “A” (0%TiO2) and type “E” (10%TiO2) unpainted mortar showed greater differences according to the Just Noticeable Difference (JND) range caused by dirt pick up.